Diversidade de heterópteros terrestres (Insecta: Hemiptera: Heteroptera) na Serra do Japi, Sudeste do Brasil - Carrenho, Renan [UNIFESP] (2015)
It is estimated that in Brazil there are between 4,000 and 6,000 species of Heteroptera, however, knowledge about the regional fauna is still limited. For the state of São Paulo, the knowledge of the fauna of Heteroptera is scarce. The state of São Paulo is home to the largest remaining area of Atlantic Forest in the country, containing a high level of richness of species and endemism. The Atlantic Forest presents great heterogeneity of abiotic factors, including topography, temperature, humidity, soil, and radiation, ensuring a wide variety of environments and niches. In order to investigate the diversity of the terrestrial heteropteran in an area of Atlantic Forest and indentify local variables (phytophysiognomy and weather) that influence it, collections were made at Municipal Biological Reserve of Serra do Japi. An identification key for the Reserve is provided. The temperature and wind influenced the richness and abundance of the heteropterans collected in the light trap.